Electrocatalytic Properties of TiO2-Embedded Pt Nanoparticles in Oxidation of Methanol: Particle Size Effect and Proton Spillover Effect - Yoo, Sung Jong; Lee, Kug-Seung; Cho, Yong-Hun; Kim, Soo-Kil; Lim, Tae-Hoon; Sung, Yung-Eun (SPRINGER, 2011)
Size-controlled Pt nanoparticles embedded in TiO2 were prepared by simultaneous dual-gun sputtering from pure targets of Pt and TiO2. The mean diameter of the Pt nanoparticles, as confirmed by their transmission electron microscopic images, was varied from similar to 2 to similar to 4 nm by changing the RF power ratio of Pt and TiO2. The transmission electron diffraction and X-ray diffraction patterns of the Pt nanoparticles embedded in TiO2 confirmed that the Pt particles are polycrystalline, whereas the TiO2 matrix is amorphous. The electrocatalytic properties of Pt/TiO2 were strongly influenced by the particle size and the TiO2 support. The presence of the TiO2 support led to higher electronic density on Pt, changing its chemisorption properties, weakening the Pt-CO bonds, and increasing its CO oxidation activity. The high CO oxidation activity of the Pt nanoparticles embedded in TiO2 can be also attributed to the ability of TiO2 to provide highly reactive oxygen atoms. CO desorbed at higher onset potential with a decrease in the particle size, which is related to quantum-size effects in the Pt nanoparticles. The high activity of methanol oxidation on the Pt/TiO2 electrode resulted from the homogeneous dispersion and the miniaturization of Pt. In addition, we found that the enhanced catalytic activity in the Pt/TiO2 electrodes correlated to proton spillover phenomena in TiO2 and was measured by performing an in situ electrochromic test.
Keywords: FUEL-CELL; ELECTROCHROMIC DEVICES; ANODE CATALYSTS; PLATINUM; FILMS; PERFORMANCE; TIO2(110); ELECTRODE; ELECTROOXIDATION; CHEMISORPTION